Rancang Bangun Sistem Informasi Survei Kepegawaian Kantor Pelayanan Perbendaharaan Negara Kediri Berbasis Web - Kusuma, Selvia Ferdiana; Naufal, Mohammad Farid; Aminulloh, Septian Wijaya; Vernolyo, Panji Yumadana (STIKOM Tunas Bangsa Pematangsiantar, 2021)
The State Treasury Service Office in Kediri is one of the services of the state general treasurer in the city of Kediri. The function of the State Treasury Service Office in Kediri, which is responsible for channeling the budget according to its allocation as stipulated in the APBN Law. In order to maintain the quality of the services provided, the State Treasury Service Office in Kediri always carries out supervision. Currently, the employment survey is conducted using the google form. However, the use of this form of google is not optimal. This is because there is no final cost for the staffing survey that has been carried out and there is no report on the results of the survey that has been carried out. Therefore, this study makes a web-based design of the personnel survey information system at the State Treasury Service Office in Kediri. This information system uses the programming language PHP and Javascript (EcmaScript 6) with the MySQL database. Based on the experiments that have been done, all the features in this information system can work according to their function. The design of this information system can help the State Treasury Service Office in Kediri to conduct the performance survey process more efficiently.